Aqueous plant extracts: A strategic approach to mitigate bacterial soft rot disease in onions - M. Rahman; Md. Harun-Or-Rashid; A. Khan; A T M Morshed Alam; Sharif Ahmed (Innovations in Agriculture, 2023)
The bacterial soft rot of onion caused by Burkholderia cepacia is a major issue in subtropical storage. At BSMRAU, Bangladesh, examined plant extracts for antibacterial impact on this disease in both lab and storage contexts. Studied 11 aqueous extracts: cheerota, jute, chatim, mander, stone apple, marigold, onion garlic, neem, lime, and turmeric, for antibacterial effects against the disease. Only the extracts from jute leaf and cheerota shown antibacterial action. Extracts from the plants cheerota and jute leaf were used to combat onion soft rot. The test involved soaking onion samples and exposing to indicator bacteria after in vitro selection. Onions were stored for 22 weeks in sterile conditions. Botanical extract application notably reduced infection, weight loss, and boosted onion's percentage disease reduction (PDR). Cheerota plant extract showed the greatest inhibitory effects for controlling soft rot bacteria of onion in-vitro and in storage conditions, respectively which may be the eco-friendly management of the onion soft rot disease.